EVALUASI TATA KELOLA JAMINAN KESEHATAN NASIONAL DALAM PENGUAT PERAN PEMERINTAH DAERAH BENGKULU - Vini Restu Insani; Jon Hendri Nurdan (HUMAN CARE JOURNAL, 2022)
The role and support of the local government (Pemda) is very important in the National Health Insurance (JKN-KIS) program to encourage Universal Health Coverage (UHC) by expanding the coverage of participation, improving service quality, and increasing compliance. One of the efforts that can be made by the Regional Government in expanding participation is to integrate the Regional Health Insurance (Jamkesda) program into the JKN-KIS program. The existence of regulatory fragmentation and disharmony of membership data turned out to provide diversity to the health capacity and governance of JKN implementation in Bengkulu Province.